2017
DOI: 10.1111/1750-3841.13638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Solvents on the Measurement of Phenolics and the Antioxidant Activity of Mulberry (Morus atropurpurea Roxb.) with Accelerated Solvent Extraction

Abstract: The effects of 9 different solvents on the measurement of the total phenolics and antioxidant activities of mulberry fruits were studied using accelerated solvent extraction (ASE). Sixteen to 22 types of phenolics (flavonols, flavan-3-ols, flavanol, hydroxycinnamic acids, hydroxybenzoic acids, and stilbenes) from different mulberry extracts were characterized and quantified using HPLC-MS/MS. The principal component analysis (PCA) was used to determine the suitable solvents to distinguish between different clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
(33 reference statements)
2
21
0
1
Order By: Relevance
“…Our findings are in agreement with the studies of Przygodzka et al [7], who reported that water-ethanol (1:1) mixture was better solvent for extraction of TPC from allspice, clove and some other aromatic spices, and also Alcântara et al [25], as the highest efficiency of TPC extraction from chia seeds was observed in the binary water-ethanol solvent in comparison to water and ethanol solvents alone. As reported by others [24,26,27] water was the least efficient solvent when considering the polyphenol extraction from plant material. Time of extraction also significantly affected TPC.…”
Section: Total Phenolic Content-effects Of Solvent Time and Plant Materialsmentioning
confidence: 64%
“…Our findings are in agreement with the studies of Przygodzka et al [7], who reported that water-ethanol (1:1) mixture was better solvent for extraction of TPC from allspice, clove and some other aromatic spices, and also Alcântara et al [25], as the highest efficiency of TPC extraction from chia seeds was observed in the binary water-ethanol solvent in comparison to water and ethanol solvents alone. As reported by others [24,26,27] water was the least efficient solvent when considering the polyphenol extraction from plant material. Time of extraction also significantly affected TPC.…”
Section: Total Phenolic Content-effects Of Solvent Time and Plant Materialsmentioning
confidence: 64%
“…A comparative study where UAE and ASE were used for the extraction of total phenolic compounds from mulberry fruits was developed using nine different solvents for extraction and HPLC‐MS/MS for analysis. Additionally, principal component analysis was used to determine the most appropriate solvents and to distinguish between different classes of phenolic compounds . As a conclusion, the experimental results indicated the superiority of ASE compared with UAE.…”
Section: Extraction Techniques Used For Bioactive Components Includinmentioning
confidence: 91%
“…The highest extraction efficiency could be achieved by using 50% acidified methanol (50MA) as ASE solvents with 15.14 mg gallic acid equivalents g dry weight of mulberry fruit . The PCA results revealed that the 50MA followed by 50% acidified acetone (50AA) was the most efficient solvent for the extraction of phenolic compounds, particularly flavonols (627.12 and 510.31 μg/g dry weight, respectively), while water (W) was not beneficial to the extraction of all categories of phenolics.…”
Section: Extraction Techniques Used For Bioactive Components Includinmentioning
confidence: 99%
“…The solvent choice for extraction is the most important variable in the extraction process, as the yield and the rate of polyphenolic extraction are related to solvent characteristics. Even if methanol has been reported as being more efficient for the extraction of low-molecular weight polyphenols and acetone for the high molecular weight polyphenols, ethanol-water mixture is often considered [6,14,15,16]. Its safety and environmentally friendly character recommends it for both pharmaceutical and cosmetic applications [17].…”
Section: Introductionmentioning
confidence: 99%